Pengaruh Arus Kas, Penjualan, Perputaran Piutang Dan Hutang Lancar Terhadap Liquidity Pada Sektor Trade Company Yang Tercatat Di BEI - Ines Triastuti Lumbangaol; Elshadai Anlo Melki; Shelly Shelly; Tetty Tiurma Uli Sipahutar (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This research aims to examine and analyze the effect of cash flow, sales, turnover of accounts receivable and current payable on liquidity. The population in this study were all trade company sectors totaling 65 issuers and the sample selected based on the criteria was 22 samples using 5 years, so the data totaled 110 data. The data test technique uses classical assumptions, multiple linear regression and hypothesis testing. From the results of the data analysis shows that partially cash flow has a positive effect on liquidity, sales have a negative effect on liquidity, while turnover of accounts receivable and current payable has no effect on liquidity. Simultaneously, cash flow, sales, accounts receivable turnover and current accounts payable affect liquidity. The magnitude of the influence of the independent variables affecting liquidity is 24.7%, where the remaining 75.3% is explained by other factors such as working capital, cash turnover and inventory turnover. Keywords : Cash Flow, Sales, Receivable Turnover, Current Liabilities and Liquidity.